1966
DOI: 10.1172/jci105423
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Findings in Normal and Osteoarthritic Articular Cartilage. II. Chondroitin Sulfate Concentration and Chain Length, Water, and Ash Content*

Abstract: Softening and erosion of cartilage, the characteristic early lesions of osteoarthritis, occur in sites of decreased chondroitin sulfate concentration. The role of aging and the specific biochemical events that produce this alteration in glycosaminoglycan composition have been under study in several laboratories. Collins and McElligott found increased radiosulfate fixation in these lesions compared with normal articular cartilage from the same individuals, suggesting increased synthesis of polysaccharide (1). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
0
3

Year Published

1968
1968
1995
1995

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 210 publications
(80 citation statements)
references
References 9 publications
7
70
0
3
Order By: Relevance
“…This was apparent when the uronic acid values were related either to the water content or to the DNA content of the tissues, since these were essentially the same in unloaded cartilage as in loaded cartilage. The similarity of water content values in loaded and unloaded cartilage suggests that normal unloaded cartilage is different from atrophic (10,25) or osteoarthritic cartilage (26,27) in which the uronic acid content is decreaseld but the water content is increased. Presumably, the hyperhydration in damaged cartilage reflects an abnormality in the collagen network of the tissue that permits the hydrophilic proteoglycans to expand their molecular domains (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…This was apparent when the uronic acid values were related either to the water content or to the DNA content of the tissues, since these were essentially the same in unloaded cartilage as in loaded cartilage. The similarity of water content values in loaded and unloaded cartilage suggests that normal unloaded cartilage is different from atrophic (10,25) or osteoarthritic cartilage (26,27) in which the uronic acid content is decreaseld but the water content is increased. Presumably, the hyperhydration in damaged cartilage reflects an abnormality in the collagen network of the tissue that permits the hydrophilic proteoglycans to expand their molecular domains (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…These sites of cartilage softening and erosion have a decreased concentration of hexosamine,26 sulfate,le chondroitin sulfates, 6 and, in more advanced lesions, keratan sulfate,s in comparison to normal cartilage sites from the same joints. Protein extracted along with the polysaccharide is not significantly decreased in concentration, even in more advanced lesions; collagen concentration is also unaltered in these lesions6 Erosion of the cartilage means loss of the entire cartilage substance, collagen and all.…”
Section: Biochemical and H/letabolic Aspecxs Of The Pathogenesis Of Omentioning
confidence: 93%
“…DISCUSSION An in vitro adult rabbit articular cartilage organ model has been reported. Dziewiatkowski and others (1)(2)(3)(4)(5)13,14) have clearly shown that 90% plus of s 5 S 0 , is incorporated into glycosaminoglycans and that its incorporation is related to the rate of synthesis. By utilizing this technique we have shown that the articular cartilage slices and floating plugs have the property of a constant rate of 35S0, incorporation into glycosaminoglycans from day 7 to day 14.…”
Section: Thementioning
confidence: 95%